The SOUDAN 2 detector - The operation and performance of the tracking calorimeter modules - Allison, W; Alner, G; Ambats, I; Ayres, D; Balka, L; Barr, G; Barrett, W; Benjamin, D; Bode, C; Border, P; Brooks, C; Cobb, J; et al. (1996)
SOUDAN 2 is a 960-ton tracking calorimeter which has been constructed to search for nucleon decay and other phenomena. The full detector consists of 224 calorimeter modules each weighing 4.3 tons. The modules consist of finely segmented iron instrumented with 1 m long drift tubes of 15 mm internal diameter. The tubes enable three spatial coordinates and dE/ dx to be recorded for charged particles traversing the tubes. The spatial resolution is 0.38 cm in the x-y plane and 0.65 cm in the z, or drift, direction. The operation and performance of the modules are discussed.